DNA methylation changes on immune cells in Systemic Lupus Erythematosus - Carolina Hurtado; Liliana Yazmín Acevedo Sáenz; Elsa María Vásquez Trespalacios; Rodrigo Urrego; Scott Jenks; Iñaki Sanz; Gloria Vásquez (Taylor & Francis Group, 2020)
DNA methylation as a process that regulates gene expression is crucial in immune cells biology. Global and gene specific methylation changes have been described in autoimmunity, especially in Systemic Lupus Erythematosus. These changes not only contribute to the understanding of the disease, but also some have been proposed as diagnostic or disease activity biomarkers. The present review compiles the most recent discoveries on this field on each type of immune cells, including specific changes in signalling pathways, genes of interest and its possible applications on diagnosis or treatment.